Accessibility and utilization of information on maternal nutrition : a case study of Butembe County, Jinja District - Nsibirano, Ruth (Kampala, 1997)
Thesis (M.A. Women Stud.) - Makerere University, 1997.
Includes bibliographical references (p. 127 - 134)
Keywords: Mothers -- Nutrition information services -- Uganda -- Jinja Distric t; Maternal nutrition -- Information services -- Uganda -- Jinja Distri ct